2017
DOI: 10.4236/msa.2017.82011
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Effects on Interlaminar Fracture Behavior in Carbon Fiber-Reinforced Polymer Composites

Abstract: Fiber-reinforced polymer composite materials have become materials of choice for manufacturing application due to their high specific stiffness, strength and fatigue life, low density and thermal expansion coefficient. However, there are some types of defects such as porosity that form during the manufacturing processes of composites and alter their mechanical behavior and material properties. In his study, hand lay-up was conducted to fabricate samples of carbon fiber-reinforced polymer composites with three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
0
15
0
2
Order By: Relevance
“…In particular, with higher stretch ratio of R = 4 × 4 shown in Figure (e), the short fibrillar slit‐like porous structures grow with crack and porosity in both stretching directions. As known, more porosity in PVDF film would reduce material strength and resistance to crack propagation as well . Though the porosity and the crack do not have significant influence on the piezoelectric properties, these deficiencies will be a problem of quality reduction …”
Section: Resultsmentioning
confidence: 99%
“…In particular, with higher stretch ratio of R = 4 × 4 shown in Figure (e), the short fibrillar slit‐like porous structures grow with crack and porosity in both stretching directions. As known, more porosity in PVDF film would reduce material strength and resistance to crack propagation as well . Though the porosity and the crack do not have significant influence on the piezoelectric properties, these deficiencies will be a problem of quality reduction …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Costa et al [35] emphasized in their review that the interlaminar shear strength can be significantly affected if the porosity content goes beyond 0.9%. In addition, Hakim et al [36] highlighted that higher porosity levels make the composite part sensitive to water penetration and environmental factors which detrimentally impact the static and fatigue strength. The minimum void percentage that we found can be attributed to the high vacuum pressure applied during the curing process.…”
Section: Fiber Volume Fractionmentioning
confidence: 99%
“…The minimum void percentage that we found can be attributed to the high vacuum pressure applied during the curing process. Hakim et al [36] evaluated the impact of vacuum pressure on the porosity level. They examined three levels of vacuum pressure: poor (0 mmHg), medium (330 mmHg), and high (686 mmHg) and concluded that poor vacuum pressure induces 3.43% of porosity versus only 1.43% with high vacuum pressure.…”
Section: Fiber Volume Fractionmentioning
confidence: 99%
“…The effect of the porosity on the mechanical behavior of polymer composites is under the interest of many researchers. For example, Hakim et al [23] reported the influence of porosity on the interlaminar fracture behavior in carbon-fiber-reinforced polymer composites. Specifically, the increase of porosity led to the decrease in both interlaminar fracture toughness and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%